Prediction of protein content in rice using a near-infrared imaging system as diagnostic technique - Lin, Lian-Hsiung; Lu, Fu-Ming; Chang, Yung-Chiung (International Journal of Agricultural and Biological Engineering, 2019)
The aim of this research was to determine the rice protein content utilizing a NIR imaging system. The developed imaging system utilized a NIR camera which installed automatically exchanged filters with the wavelength range from 870 nm to 1014 nm. Multiple liner regression (MLR), partial least square regression (PLSR), and artificial neural network (ANN) models were employed as data analysis methods for 6.18%-9.43% rice protein detections within both the NIR imaging system and commercial NIRS. A total of 180 rice samples were used in this study, of which 120 random samples were selected as a calibration set for the MLR and PLSR models. Moreover, for establishing the back-propagation ANN model, the same 120 samples were divided into two parts, 80 samples were used for network training and the other 40 were established as the monitoring set. To compare with the results of MLR, PLSR, and ANN models, the remaining 60 of the total 180 samples were established as the validation set. Applying an MLR linear regression model composed of five wavelengths; the NIR imaging system successfully detected rice protein content. The predicting results of rval2 and SEP were 0.769 and 0.294%, respectively. In PLSR model, utilizing the imaging system obtained the results of rval2 = 0.782, and SEP = 0.274% within the wavelength range from 870 nm to 1014 nm. Five significant wavelengths selected by the MLR model were the same as the input data of the ANN model, and the prediction results were rval2 = 0.806, and SEP = 0.266%. The prediction results indicated that the developed NIR imaging system has the advantages of simple, convenient operation, and high detection accuracy as well as it presents commercial potential in non-destructive detection of rice protein content. Keywords: non-destructive detection, near-infrared imaging system, inner quality, rice, protein content, agriculture product DOI: 10.25165/j.ijabe.20191202.4709 Citation: Lin L-H, Lu F-M, Chang Y-C. Prediction of protein content in rice using a near-infrared imaging system as diagnostic technique. Int J Agric & Biol Eng, 2019; 12(2): 195–200.